Answer:
x = -6/5
Explanation:
Note that 2 log-to-the-base-2 of 3 is equivalent to log-to-the-base-2 of 3^2, or log-to-the-base-2 of 9.
Also: log-to-the-base-2 of 9 + log-to-the-base-2 of (x + 1) is equivalent to
log-to-the-base-2 of 9(x + 1), and thus we have:
log-to-the-base-2 of 9(x + 1) = log-to-the-base-2 of (4x + 3)
And so:
log-to-the-base-2 of 9(x + 1) log-to-the-base-2 of (4x + 3)
2 = 2
Because this is true, we can conclude that 9(x + 1) = (4x + 3).
Combining like terms results in 5x + 9 = 3, or 5x = -6. Then x = -6/5